Leveraging Social Protection Programs for Improved Nutrition : Report on the Proceedings of the Global Forum on Nutrition-Sensitive Social Protection Programs, 2015 - Spray, Andrea L. (World Bank, Washington, DC, 2016)
The Global Forum on Nutrition-Sensitive Social Protection Programs,co-hosted by Secure Nutrition and the Russian Federation Ministry of Finance,was held in Moscow, Russia on the 10th and 11th of September, 2015. Theevent drew approximately 150 participants from over twenty countries, and provided a space for in-depth conversations anchored to country case studies that featured programs integrating social protection instruments and nutrition principles. The role of effective nutrition-sensitive social protection programs has been increasing, and the current global development agenda calls for the profile of nutrition to be raised by ensuring strong leadership and commitment at alllevels and across multiple sectors. Partnerships are playing an increasinglyimportant role in the development of assistance architecture. The GlobalForum on Nutrition-Sensitive Social Protection Programs (Global Forum)aimed to support these efforts by contributing to the evidence base for policyoptions and operational actions. Objectives and Achievements are follows i) Better understand existing needs of countries to assist them in settingup well-functioning nutrition-sensitive social protection programs; (ii) Support countries in catalyzing, building commitment for, designing,establishing, managing, and scaling up nutrition-sensitive social protectionprograms through providing technical assistance and capacitydevelopment to governments; (iii) Disseminate best policies and practices and innovative approaches inthe area of social protection systems linking food security and nutrition,poverty reduction, and agricultural production; (iv) Improve access to knowledge and build awareness related to nutrition-sensitive social protection through presentation of existing internationalinitiatives, knowledge platforms and tools, including theSecureNutrition Knowledge Platform; (v) Facilitate South-South and Triangular Cooperation and exchange ofexperience and lessons learned among countries, allowing them to identify their own pathways in developing nutrition-sensitive socialprotection programs specific to their national needs; (vi) Enhance coordination and cooperation among development partnersand international organizations to harness the resources of a diverserange of actors involved in nutrition-sensitive social protectionprograms; (vii) Promote engagement of all-interested stakeholders, including governments,private sector, civil society, NGOs, international and regionalorganizations, and other development partners in designing andimplementing nutrition-sensitive social protection programs.